HARMONIC ANALYSIS OF DISTRIBUTED ENERGY SOURCES USING SLIDING FFT AND IEC 61000-4-7 (REVUE ROUMAINE DES SCIENCES TECHNIQUES — SÉRIE ÉLECTROTECHNIQUE ET ÉNERGÉTIQUE, 2025)
This paper presents the results of harmonic analysis of the current and voltage signals measured in the points of common coupling (PCC) to the distribution networks of several distributed energy sources. One small hydro (HPP) and four small photovoltaic (PV) power plants are considered. Voltage and current harmonics are calculated in two ways: 1) as per standard IEC 61000-4-7, and in accordance with IEEE 519 and EN 50160, and 2) by sliding fast Fourier transform (SFFT), which is applied to calculate time-varying current and voltage harmonics in the specific recorded signals. Application of IEEE 519 and EN 50160 yields different results and conclusions due to different calculation procedures and limiting values. PV power plants can generate almost sinusoidal currents when operating with high power, while the HPP can generate currents with strongly distorted waveshapes when supplying large nonlinear loads. As a result, all four PV power plants meet the requirements for current and voltage harmonics, whereas the analyzed HPP does not meet some of the defined limits. The SFFT analysis confirms the feasibility of dynamic real-time harmonic monitoring, which can play a crucial role in modern distribution networks.
Keywords: EN 50160; Fast Fourier transform (FFT); Harmonics; Hydro power plant; IEEE 519; Photovoltaic (PV) power plant